Influence of the post-processing operations on surface integrity of metal components produced by laser powder bed fusion additive manufacturing: a review - KAYNAK, YUSUF (TAYLOR & FRANCIS INC, 2020)
As industries are increasingly adopting the laser powder bed fusion (LPBF) additive manufacturing (AM) process, it is crucial to understand the process closely and to find ways to improve the final quality of the finished parts. The LPBF process is capable of producing tailored designs, which are lighter in weight and having strength comparable to conventional components. However, the acquired surface texture and some of the mechanical properties of LPBF-produced components are still sub-standard compared to the conventional components. As of now, the post-processing technique is witnessed as the only sustainable approach to enhance the mechanical and microstructural performance of the additive products since any further optimization of the LPBF processing parameters is reported inefficient in bringing the relevant changes in the as-built LPBF parts. So far, several post-processing techniques such as thermal, mechanical, and/or chemical-based have been applied to different additive materials, and the results have been beneficial. This article reviews the effects of post-processing operations on the surface integrity properties of as-built LPBF parts, namely surface roughness, microhardness, microstructure, mechanical strength, corrosion, and wear resistance. The results of the post-processing operations are also discussed and compared with the as-built and conventional conditions for different engineering materials.
Keywords: Additive manufacturing; laser powder bed fusion; post-processing operations; surface integrity